The Influence of PAK Teachers' Example on the Personality of Class VIII Students of SMP Negeri 3 Tarutung, North Tapanuli Regency for the 2023/2024 Academic Year - Lilis Suganda Sihotang; Taripar Aripin Samoir; Damayanti Nababan (Intellektika : Jurnal Ilmiah Mahasiswa, 2023)
The purpose of this study was to determine the influence of the example of PAK teachers on the personality of grade VIII students at SMP Negeri 3 Tarutung, North Tapanuli Regency for the 2023/2024 academic year. The method used in this study is a quantitative research method with descriptive and inferential statistical approaches. The population is all grade VIII students of SMP Negeri 3 Tarutung, North Tapanuli Regency for the 2023/2024 academic year who are Christians, totaling 180 people and a sample of 54 people was determined from the total population using the proportional random sampling technique according to strata (Proportionate Staratifiet Random Sampling). Data was collected with a positive closed questionnaire of 46 items where 26 items were for variable X and 20 items for variable Y. The results of the data analysis showed that there was a positive and significant influence on the role model of PAK teachers on the personality of grade VIII students at SMP Negeri 3 Tarutung, North Tapanuli Regency for the 2023/2024 academic year: 1) Influence Test: obtained regression equation Y ̂=32.38+0.49X.b) From the linear regression test, it can be proven that the influence of variable X (PAK Teacher Example) on variable Y (Student Personality) is positive because the regression coefficient (β) = 0.49, Furthermore, the t test to test the significance of the regression coefficient (B) obtained tcalculate = 5.008 > ttable which is 2.000. Thus, Ha is that there is a positive and significant influence on the role model of PAK teachers on the personality of grade VIII students at SMP Negeri 3 Tarutung, North Tapanuli Regency for the 2023/2024 academic year, accepted and H0 rejected.